2008
DOI: 10.1136/hrt.2008.148742
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of oxygen in the treatment of myocardial infarction: systematic review

Abstract: Context: International guidelines recommend the routine use of oxygen therapy in the treatment of myocardial infarction (MI). Objective: To undertake a systematic review and metaanalysis of randomised placebo-controlled trials of oxygen therapy in MI. Data sources: Medline, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, EMBASE and CINHAL. Study selection: Randomised placebo-controlled trials of oxygen therapy in MI. Data extraction: The primary clinical outcome was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
1
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 51 publications
0
88
1
9
Order By: Relevance
“…3 Adverse outcomes of hyperoxemia were identified in patients after cardiac arrest 6 and acute myocardial infarction 7 and in extremely premature infants. 8 Animal studies have demonstrated that high F IO 2 increases free radicals and causes an influx of inflammatory cells in the lung, 9 pulmonary permeability, and endothelial cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…3 Adverse outcomes of hyperoxemia were identified in patients after cardiac arrest 6 and acute myocardial infarction 7 and in extremely premature infants. 8 Animal studies have demonstrated that high F IO 2 increases free radicals and causes an influx of inflammatory cells in the lung, 9 pulmonary permeability, and endothelial cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…5 The investigators concluded that the ''limited evidence that exists suggests that the routine use of high-flow normobaric oxygen in uncomplicated myocardial infarction may result in a greater infarct size and possibly increase the risk of mortality. ''…”
Section: Some Recent Literature Related To Oxygen Therapy Of Amimentioning
confidence: 99%
“…Oxygen should be administered to patients with breathlessness and/or clinical signs of heart failure and/or cardiogenic shock (CS), and continuous positive airway pressure or endotracheal intubation with ventilatory support may be required. 16 …”
Section: Pre-hospital Management Of Stemi Complicationsmentioning
confidence: 99%